Dynamic modeling, stability analysis and control of interconnected microgrids: A review. (15th March 2023) - Naderi, Mobin; Khayat, Yousef; Shafiee, Qobad; Blaabjerg, Frede; Bevrani, Hassan
Abstract: This paper reviews concepts of interconnected microgrids (IMGs) as well as compare and classify their modeling, stability analysis, and control methods. To develop benefits of isolated microgrids (MGs) such as reliability improvement and their renewable energy integration, they should be interconnected, share power, support the voltage/frequency of overloaded MGs, etc. Despite maximizing their benefits and decreasing weaknesses of isolated MGs, IMGs require maintaining stability in different operation modes and employing appropriate control methods. Moreover, a basic requirement for stability analysis and controller design is system modeling. Since many articles have addressed these topics on IMGs from different views, a comparison is necessary. Therefore, IMG dynamic modeling methods are classified and their main features and challenges are discussed. Then, stability analysis and control methods of IMGs are reviewed and compared. The provided review is supported by conceptual diagrams, classification tables, off-line and real-time simulations using MATLAB and OPAL-RT simulator for comparison. Furthermore, a data set is provided to study fundamentals as well as research gaps, which are addressed for future works. Graphical abstract: Highlights: Conceptual classifications of dynamic modeling, stability and control of multi-MGs. Comprehensive literature reviews and correlated research gaps for future research work. Comparison of dynamic modeling methods using eigenvalue/sensitivity analysis. Off-line/real-time simulations to study power exchange/sharing stability and control.